VERNAKULARISASI PEMAHAMAN HADIS (Refleksi Wacana Islam Nusantara) - Muhammad Zubir; Mushallina Hilma (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
The term vernacular is born because of an understanding of religious texts taking into account the conditions of the Indonesian Islamic community. This understanding is known as the context of the understanding of hadith which is an effort made by the ulama as one of ijtihad in examining the content of the hadith of the hadith. This is done if there is a hadith that appears to be incompatible with the condition of a society or a certain period of time. The hadith about the leader from the Quraysh tribe and the hadith about not going to succeed in a people if the leadership is left to women is an example of how difficult it is to be applied in Indonesia if it is only understood textually and not understood by a contextual approach. In Indonesia, many hadiths that require new explanations (syarah) in order to be able to uncover various biological essence, using language that is popular and in line with present-day logic, to make it easier to achieve goals. Therefore, Islamic scholars, especially in Indonesia are required to be ready to anticipate the emergence of actual problems that develop in society.